Pengaruh Persepsi Penghargaan Finansial dan Pemahaman Ajaran Tri Pantangan Terhadap Pemilihan Profesi sebagai Akuntan Publik Pada Mahasiswa Akuntansi Fakultas Ekonomi Universitas Sarjanawiyata Tamansiswa Yogyakarta - Teguh Erawati; Maria Barek Welan (Yayasan Literasi Ilmiah Indonesia, 2022)
Purpose: This study aims to examine whether the perception of financial rewards and understanding of the three taboos has an effect on the choice of the public accounting profession for Accounting students, Faculty of Economics, Universitas Sarjanawiyata Tamansiswa Yogyakarta. Method: The method of collecting data in this study is using a questionnaire or questionnaire. The study took a sample of 85 accounting students from the Faculty of Economics, Universitas Sarjanawiyata Tamansiswa Yogyakarta. The sampling technique used snowball sampling. Data was collected by distributing questionnaires in the form of a google form questionnaire to be distributed to other respondents with the aim of obtaining data from respondents. The number of questionnaires that were processed were 85 questionnaires. Data were analyzed using multiple linear regression analysis. Finding: The results of this study indicate that financial rewards have a positive effect on the selection of the public accounting profession and the variable understanding of the three taboos has a positive effect on the selection of the public accounting profession. Novelty: This study adds to the understanding of the three taboos variable to prove how the students of the Bachelorwiyata Tamansiswa university can implement Tamansiswa's teachings in a career in the field of public accounting.